PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA (Pada kantor dinas kependudukan dan pencatatan sipil kabupaten malang) - Noer Muamal; Hadi Sunaryo; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
AbstractThe objective of this research is to perceive the affect of the quality in term of working and commitment organization towards the satisfaction of working at dispenduk office and capil in the district of malang. The research is done by using quantitative approach and compiling the data through questionnaire. The scope of population in this research is all the employee working for population civil and also employee working for civil regristation in malang district. The technic used for sampling data is saturated sampling, whereas all the population is a sample for the research that is add up to 99 entities. The method that is being used is instrument test, normality test, multiple linear regression analysis. Classical assumptions, and hypothesis testing using SPSS 14 for Windows.The outcome of this research shows the quality of working life and organizational commitment have great affect partially and altogether with the satisfactory of working.Key word: work satisfaction, quality of working life, and organizational commitment.